Quel type de gestualité pour la comédie ancienne? - Capponi, Matteo (Synthesis.)
What kind of gestures were used in ancient comedy? Iconography gives us an idea of the body and costume of the comic actor. But beyond the fixity of images, how were gestures successively performed on stage?To answer this question, we need to consider the material context in which the plays were produced: the costumes, the masks, the rectangular orchestra, and the large audience. We must remember that gesture is above all a medium adapted to the space and to technical needs.In this article, I'd like to check whether the method I've applied so far to analyze kinesics in tragedy also works in the case of comedy. I study a scene from Aristophanes' Acharnians characterized by intense moves. I show that different types of gestures can be identified in the text: praxis gestures, modal gestures, mimetic gestures, and iconic gestures. Taken together, they allow us to better understand what the Athenian spectators had "in front of their eyes".